Dimensi Konsep Diri Remaja Penyintas Kanker di Yayasan Kasih Anak Kanker Indonesia Riau - Rika Zahara; Welly Wirman; Nurjanah Nurjanah (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze the dimensions of self-concept among adolescent cancer patients at the Indonesian Childhood Cancer Foundation (Yayasan Kasih Anak Kanker Indonesia/YKAKI) Riau Branch based on the physical, psychological, and social dimensions through their lived experiences during the treatment process. This study employed a qualitative approach using the participatory and phenomenological Community-Based Research (CBR) method. Data were collected through in-depth interviews, observations, and documentation, and were analyzed using descriptive-interpretative analysis with source triangulation to ensure data validity. The results show that the self-concept of adolescent cancer patients was formed through physical, psychological, and social dimensions. Physically, changes in appearance caused by cancer and chemotherapy led to feelings of being different, embarrassment, and decreased self-confidence. Psychologically, the adolescents experienced denial, anxiety, sadness, and fear, but gradually developed self-acceptance through the adaptation process. Socially, support from family, peers, and the surrounding environment played an important role in enhancing self-acceptance, self-confidence, and positive social interactions.